An Intelligent Design of Wireless Powering in Agricultural Sensor Networks - Abirami T, Nivethitha G, Ramya S, Priyadharshini S (International Journal of Modern Agriculture, 2021)
In the field of decision agriculture, energy efficiency is essential for the long operation of wireless communication nodes. Energy harvesting and wireless power transfer strategies are discussed in this project, and including these applications in Wireless Sensor Networks (WSN).WSN has gained a lot of popularity and application as a base support for the Internet of Things (IoT). In intelligent agriculture, for example, we would use a sensor network to collect data on crop growth and other factors. The difficulty in supplying power to wireless nodes, on the other hand, has severely hampered IoT application and growth. sOn the nodes, people use low-power sleep scheduling and other energy-saving methods to solve this problem. Despite the fact that these techniques can extend the working time of nodes, they will ultimately become ineffective due to energy exhaustion. This project proposes a three-layer Wireless Energy Powering (WEP) framework for data collection in rechargeable WSN to keep the node running forever, called WEP, which includes the input sensor layer, renewable energy PV panel layer, and mobile station layer. A distant base station (BS) is also included in the WEP rechargeable layer to monitor the status of the project through IoT. In addition, the framework will reduce the system’s total energy consumption. Such energy harvesting techniques led to the development of an efficient wireless network communication system to energy Sensor networks in decision agriculture for extended field operation.